Effect of Bacillus subtilis IMV B-7023 on the Accumulation of Biologically Active Substances in Wheat Root Exudates - Kurdish, I.K.; Chobotarov, A.Yu.; Brovarska, O.S.; Chobotarova, V.V.; Parkhomenko, N.Y.; Kharkhota, M.A.; Курдиш, І.К.; Чоботарьов, А.Ю.; Броварська, О.С.; Чоботарьова, В.В.; Пархоменко, Н.Й.; Хархота, М.А. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
As plants grow, up to 40% of their photosynthetic products are released into the root zone. These root exudates have a significant impact on the formation of the plant rhizosphere microbiome. However, the effect of introduced microorganisms on plant root exudates is not well understood. The aim of this study was to determine the effect of Bacillus subtilis IMV B-7023 on the accumulation of exometabolites in the hydroponic environment of wheat plants. Methods. The study of the effect of B. subtilis on the accumulation of biologically active substances in root exudates was carried out on the wheat variety Shestopalivka. Morphometric parameters of plants were determined. Protein content in the medium was determined by the Bradford method, carbohydrates – by interaction with phenol and sulfuric acid, and phenols – by Folin-Cocalteu reagent. Results. It was shown that bacterization of wheat seeds with B. subtilis bacteria significantly increased the accumulation of carbohydrates, protein and phenols in the medium. The most noticeable effect on the accumulation of these compounds in the medium was observed after bacterization with a suspension containing 108 CFU/mL. Conclusions. Inoculation of wheat seeds with Bacillus subtilis IMV B-7023 significantly stimulates the accumulation of a few exometabolites in the plant growth medium: carbohydrates and protein and phenolic compounds.